Predicting potential microbe-disease associations with graph attention autoencoder, positive-unlabeled learning, and deep neural network - Peng, Lihong; Huang, Liangliang; Tian, Geng; Wu, Yan; Li, Guang; Cao, Jianying; Wang, Peng; Li, Zejun; Duan, Lian (Frontiers in Microbiology, 2023)
Background: Microbes have dense linkages with human diseases. Balanced microorganisms protect human body against physiological disorders while unbalanced ones may cause diseases. Thus, identification of potential associations between microbes and diseases can contribute to the diagnosis and therapy of various complex diseases. Biological experiments for microbe-disease association (MDA) prediction are expensive, time-consuming, and labor-intensive. Methods: We developed a computational MDA prediction method called GPUDMDA by combining graph attention autoencoder, positive-unlabeled learning, and deep neural network. First, GPUDMDA computes disease similarity and microbe similarity matrices by integrating their functional similarity and Gaussian association profile kernel similarity, respectively. Next, it learns the feature representation of each microbe-disease pair using graph attention autoencoder based on the obtained disease similarity and microbe similarity matrices. Third, it selects a few reliable negative MDAs based on positive-unlabeled learning. Finally, it takes the learned MDA features and the selected negative MDAs as inputs and designed a deep neural network to predict potential MDAs. Results: GPUDMDA was compared with four stat-of-the-art MDA identification models (i.e., MNNMDA, GATMDA, LRLSHMDA, NTSHMDA) on the HMDAD and Disbiome databases under 5-fold cross validations on microbes, diseases, and microbe-disease pairs. Under the three 5-fold cross validations, GPUDMDA computed the best AUCs of 0.7121, 0.9454, and 0.9501 on the HMDAD database, and 0.8372, 0.8908, and 0.8948 on the Disbiome database, respectively, outperforming the other four MDA prediction methods. Asthma is the most common chronic respiratory condition and affects approximately 339 million people worldwide. Inflammatory bowel disease is a class of globally chronic intestinal disease widely existed in the gut and gastrointestinal tract and extraintestinal organs of patients. Particularly, inflammatory bowel disease severely affects the growth and development of children. We used the proposed GPUDMDA method and found that enterobacter hormaechei had potential associations with both asthma and inflammatory bowel disease and need further biological experimental validation. Conclusion: The proposed GPUDMDA demonstrated the powerful MDA prediction ability. We anticipate that GPUDMDA help screen the therapeutic clues for microbe-related diseases.